2021
DOI: 10.3748/wjg.v27.i17.2025
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma progression in hepatitis B virus-related cirrhosis patients receiving nucleoside (acid) analogs therapy: A retrospective cross-sectional study

Abstract: BACKGROUND Antiviral therapy cannot completely block the progression of hepatitis B to hepatocellular carcinoma (HCC). Furthermore, there are few predictors of early HCC progression and limited strategies to prevent progression in patients with HBV-related cirrhosis who receive nucleos(t)ide analog (NA) therapy. AIM The study aim was to clarify risk factors and the diagnostic value of alpha-fetoprotein (AFP) for HCC progression in NA-treated hepatitis B virus (HBV)-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Furthermore, higher PIVKA-II levels in non-viral HCC patients may result from more rigorous ultrasound surveillance, leading to the detection of more advanced disease at the time of initial diagnosis [28]. Previous studies have indicated a positive correlation between both AFP and PIVKA-II levels and tumor size [29][30][31]. Consistent with these ndings, our study identi ed tumor size as an independent factor associated with abnormally elevated levels of PIVKA-II and AFP in HCC patients.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, higher PIVKA-II levels in non-viral HCC patients may result from more rigorous ultrasound surveillance, leading to the detection of more advanced disease at the time of initial diagnosis [28]. Previous studies have indicated a positive correlation between both AFP and PIVKA-II levels and tumor size [29][30][31]. Consistent with these ndings, our study identi ed tumor size as an independent factor associated with abnormally elevated levels of PIVKA-II and AFP in HCC patients.…”
Section: Discussionsupporting
confidence: 87%
“…AFP is the most widely used biomarker for HCC, even though it has been reported that up to 20% of HCC patients’ tumor cells do not secrete AFP proteins ( 4 ). A previous study reported that a cutoff value of AFP of 90.0 ng/mL had a sensitivity of 0.609, and specificity of 0.818 for diagnosing HCC in 121 enrolled patients, and the receiver operating characteristic (ROC) curve of AFP for diagnosis of HCC was 0.746 (95% CI: 0.674–0.818) ( 5 ). Serum AFP level can indirectly reflect the ability of tumor cells to synthesize and process AFP protein.…”
Section: Introductionmentioning
confidence: 99%